NANOTECHNOLOGY IN OUR LIVES - Noor Mahommoud Naji; Nidaa Adeanan Abu Serag; Rasha Kadhim Mahdi; Rasha Kadhim Mahdi; Anmar M. K. Al- Maamori (European Journal of Agricultural and Rural Education, 2024)
Nanotechnology plays a crucial role in contemporary agriculture, serving as one of its most vital tools. It is expected that agricultural food nanotechnology will become a driving economic force soon, as nano fertilizers (thanks to their high surface energy and chemical activity) provide protection for plants, control their growth, detect diseases, increase the production rate, and improve their quality. In addition to being economical, using slow fertilizers has become a new trend to save fertilizer consumption and reduce environmental pollution. Nanoparticles or direct products can clean up hazardous waste sites, protect water, treat pollutants, or detect and monitor environmental pollutants. This review explains the use of nanomaterials in our lives and their classification and manufacturing methods.